Single cell sequencing revealed the mechanism of PD-1 resistance affected by the expression profile of peripheral blood immune cells in ESCC - Deng, Ting; Wang, Huiya; Yang, Changliang; Zuo, Mengsi; Ji, Zhi; Bai, Ming; Ning, Tao; Liu, Rui; Wang, Junyi; Ge, Shaohua; Zhang, Le; Ba, Yi; et al. (Frontiers in Immunology, 2022)
Background Esophageal squamous carcinoma (ESCC) is a highly lethal malignancy with poor prognosis. The effect of transcriptome characteristics of patient immune microenvironment (TME) on the efficacy of immunosuppressive agents is still poorly understood. Methods Here we extracted and isolated immune cells from peripheral blood of patients with PD-1 monoclonal antibody sensitivity and resistance, and conducted deep single-cell RNA sequencing to describe the baseline landscape of the composition, lineage, and functional status of infiltrating immune cells in peripheral blood of patients with esophageal cancer. Results The transcriptome characteristics of immune cells were comprehensively analyzed, and the dynamic changes of cell percentage, heterogeneity of cell subtypes and interactions between cells were explained. Co-expression and pedigree tracking based on T-cell antigen receptors revealed a significant proportion of highly migratory intertissue-effector T cells. GO and KEGG enrichment pathway Analysis of CD8+ effect-T cells ESCC_S group and ESCC_D1,2 group, found that in the up-regulated enrichment pathway, ESCC_S group enriched more PD-L1 and PD-1 checkpoint pathways expressed in tumors (JUN/NFKBIA/FOS/KRAS/IFNG), which also exist in T cell receptor signaling pathways. MT2A, MT2X and MT2E were differentially expressed in ESCC patients with PD1 mMAB resistance, which may be related to the resistance of PD-1 mMAB. Conclusions This study has an in-depth understanding of the influence of peripheral immune cell infiltration on the sensitivity of monoclonal antibody PD-1 in patients with esophageal cancer, which is helpful to promote the immunotherapy of patients with esophageal cancer.